Severe Osteogenesis Imperfecta in Cyclophilin B–Deficient Mice - Choi, Jae Won (Public Library of Science, 2009)
Osteogenesis Imperfecta (OI) is a human syndrome characterized by exquisitely fragile bones due to osteoporosis. The majority of autosomal dominant OI cases result from point or splice site mutations in the type I collagen genes, which are thought to lead to aberrant osteoid within developing bones. OI also occurs in humans with homozygous mutations in Prolyl-3-Hydroxylase-1 (LEPRE1). Although P3H1 is known to hydroxylate a single residue (pro-986) in type I collagen chains, it is unclear how this modification acts to facilitate collagen fibril formation. P3H1 exists in a complex with CRTAP and the peptidyl-prolyl isomerase cyclophilin B (CypB), encoded by the Ppib gene. Mutations in CRTAP cause OI in mice and humans, through an unknown mechanism, while the role of CypB in this complex has been a complete mystery. To study the role of mammalian CypB, we generated mice lacking this protein. Early in life, Ppib-/- mice developed kyphosis and severe osteoporosis. Collagen fibrils in Ppib-/- mice had abnormal morphology, further consistent with an OI phenotype. In vitro studies revealed that in CypB–deficient fibroblasts, procollagen did not localize properly to the golgi. We found that levels of P3H1 were substantially reduced in Ppib-/- cells, while CRTAP was unaffected by loss of CypB. Conversely, knockdown of either P3H1 or CRTAP did not affect cellular levels of CypB, but prevented its interaction with collagen in vitro. Furthermore, knockdown of CRTAP also caused depletion of cellular P3H1. Consistent with these changes, post translational prolyl-3-hydroxylation of type I collagen by P3H1 was essentially absent in CypB–deficient cells and tissues from CypB–knockout mice. These data provide significant new mechanistic insight into the pathophysiology of OI and reveal how the members of the P3H1/CRTAP/CypB complex interact to direct proper formation of collagen and bone.